Specific Factors Predict the Risk for Urgent and Emergent Colectomy in Patients Undergoing Surgery for Diverticulitis. Issue 11 (November 2018) - Valizadeh, Neda; Suradkar, Kunal; Kiran, Ravi P.
The aim of this study was to identify preoperative characteristics that may determine the need for emergency surgery for diverticulitis and assess postoperative outcomes for these patients when compared with elective surgery. All patients included in the ACS-NSQIP–targeted colectomy database from 2012 to 2013 who underwent colectomy with an underlying diagnosis of diverticulitis were included. Preoperative characteristics and 30-day postoperative outcomes were evaluated for patients who underwent elective versus emergent/urgent surgery using univariable and multivariable analyses. Of 8708 patients with diverticular disease, 28.1 per cent underwent emergent/urgent colectomy. Patients who underwent emergent/urgent colectomy had greater preoperative steroid use, diabetes mellitus, disseminated cancer, chronic renal failure, hypertension, chronic heart failure, chronic liver disease, COPD, and dependent functional health status ( P < 0001). There were more patients with age >65 years ( P < 0001), smoking history ( P < 0.05), and BMI < 18.5 kg/m 2 ( P < 0001) in the emergent/urgent colectomy group. After performing multivariable analysis, preoperative steroid use, weight loss >10 per cent, BMI < 18 kg/m 2, smoking, age > 65, and comorbid conditions were associated with a higher rate of emergent/urgent surgery. Mortality (5.2% vs 0.2%) and infectious and noninfectious complications were higher after nonelective colectomy. Emergent/urgent colectomy was also associated with longer hospital stay and reoperation. Emergency and urgent colectomy for diverticulitis is associated with significantly worse outcomes than after elective surgery, and patients with comorbid conditions who develop attacks of diverticulitis may in fact be the population that might best benefit from a lower threshold for an elective colectomy.